Vaginal Prolapse in a Handicapped, Multiparous Wild Chimpanzee in Budongo Forest Reserve, Uganda - Asiimwe, Caroline; Reynolds, Vernon; Zziwa, Paul; Mugabe, Timothy; Walumbe, Wyclif; Muhanguzi, Geoffrey; Babweteera, Fred; Zuberbühler, Klaus (African Primates, 2014)
The propensity of human females to develop vaginal prolapse is related to age, number of births, neonatal birth weight, genetics and other factors. Here, we report on a vaginal prolapse in a 33-year old, multiparous, handicapped wild chimpanzee (Pan troglodytes schweinfurthii), following her sixth delivery. Compared to the other 22 parous females of the Sonso community, the subject exhibited a high number of births within a short time period. Thus, the possible cause for her condition may have been the high number of vaginal births combined with the size and weight of the neonate. Additional possible factors not investigated here are: the impact of prolonged stage-two labour, persistent straining and genetic factors. The female fully recovered within 15 days and exhibited no unusual behavioural patterns or physiological abnormalities during recovery. We conclude that vaginal prolapse is not restricted to humans but also occurs in our closest relatives, the chimpanzees.
Keywords: Pan troglodytes schweinfurthii; Vaginal prolapse; Parity; Health monitoring; Budongo Forest Reserve